Psikoedukasi Pada Karyawan Coffee Shop Ruang Publik Dalam Upaya Pemberian Pelayanan Prima Pada Konsumen - Rodia Afriza; Rahmat Syaibani; Fenty Zahara Nasution (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This One way for a company to survive in the midst of increasingly fierce competition is to provide satisfactory service to consumers. Consumers who feel their needs are being met will not move to another place. Therefore, the company must have employees who are ready to provide excellent service or what is commonly referred to as excellent service to consumers. In providing excellent service as an effort to achieve customer satisfaction and loyalty, the company that provides services can be guided by the service excellence variables, namely: Ability, Attitude, Appearance, Attention. ), Action (Action), Responsibility (Accounttability). The application of the principles of excellent service aims to improve service to customers or consumers so that they are more optimal and able to achieve company goals.